CETAR (Content Creation Training): Meningkatkan Nilai Pasar Produk Alas Kaki di Desa Cangkuang Wetan Kabupaten Bandung - Dumanauw, Josh Samuel; Halim, Kevin Gunawan; Jenifer, Jenifer; Sihombing, Heriyandi Pandapotan; Here, Imanuel Alexander; Hermawan, Daniel (LPPM IT Telkom Purwokerto, 2025)
In the midst digital transformation, MSMEs, especially the West Java Footwear Producers Alliance (ASPAK JABAR) in Indonesia, face new marketing challenges. This study focuses on implementing Content Creation Training (CETAR) to help ASPAK JABAR transition from contract manufacturing to retail by enhancing their digital marketing skills. CETAR includes training in copywriting, public speaking, and video editing. The implementation method of the study uses Pragmatic Action Research (PAC) approach. Results show that CETAR improves ASPAK JABAR's digital marketing abilities, including social media use, copywriting, design, public speaking, and video editing. The program positively impacts MSMEs, enhancing visibility and business opportunities. CETAR is a creative solution for digital marketing challenges, contributing to MSMEs' economic development in Indonesia.